2007
DOI: 10.1016/j.ejcts.2006.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic off-pump aortic valve replacement: does the pericardial cuff improve the sutureless closure of left ventricular access?

Abstract: The occluder is easy to use and the pericardial cuff dramatically increases its efficacy as demonstrated by a significant reduction of blood loss. The cuffed occluder opens the way for endoscopic, off-pump, transventricular aortic valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2007
2007
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…In the in vitro test, 1-min flow-through was 2860 AE 176 ml for the standard occluders and 348 AE 56 ml for preclotted occluders ( p < 0.001) with a flow reduction by a ratio of 8.2 -similarly to the decrease in blood loss by a ratio of 9.4 when using a pericardial cuff, as reported by Tozzi et al [3].…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…In the in vitro test, 1-min flow-through was 2860 AE 176 ml for the standard occluders and 348 AE 56 ml for preclotted occluders ( p < 0.001) with a flow reduction by a ratio of 8.2 -similarly to the decrease in blood loss by a ratio of 9.4 when using a pericardial cuff, as reported by Tozzi et al [3].…”
Section: Resultssupporting
confidence: 55%
“…Baseline mean blood pressure was 61 AE 15 mmHg, it decreased to 52 AE 10 mmHg during deployment and remained stable at 64 AE 12 mmHg after the procedure. Precise measurements of blood loss with standard occluders were performed by Tozzi et al previously and were found to be 800 AE 20 ml in 3 h (100 AE 5 ml in 3 h when using a pericardial cuff) [3] and were not repeated, blood loss with preclotted occluders was 100 AE 30 ml in 1 h ($80 ml during deployment).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations